Stereoselective synthesis and some properties of new chlorodiorganotin- substituted macrodiolides - Gerbino, Darío César (2012)
Radical tandem addition of dialkyltin chlorohydrides, R2SnHCl (R = n-Bu, neophyl, Ph), to TADDOL's substituted diacrylates (47) led to the corresponding products of cyclohydrostannation. The new optically active chlorodialkyltinsubstituted 11-membered macrodiolides were obtained in very good yields and with much higher stereoselectivity than that achieved with the corresponding monohydrides, R3SnH. Thus, the cyclohydrostannation of diacrylate 4 and dimethacrylate 5 lead to just one diastereomer in the first case and to an easily separable mixture of two diastereomers in the second. Reduction of the new organotin macrocycles with LiAlH4 afforded optically active organotin derivatives structurally related to glutaric acid. Oxidation of the new chlorodiorganotin-substituted macrocycles with 30% hydrogen peroxide gave the new 11-membered macrocycles 30 and 31 free of tin in an average total yield of 43.4% from TADDOL. Full 1H, 13C, and 119Sn data are also reported. © 2012 American Chemical Society.